2010
DOI: 10.3727/096368909x484699
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo MRI Stem Cell Tracking Requires Balancing of Detection Limit and Cell Viability

Abstract: Cell-based therapy using adult mesenchymal stem cells (MSCs) has already been the subject of clinical trials, but for further development and optimization the distribution and integration of the engrafted cells into host tissues have to be monitored. Today, for this purpose magnetic resonance imaging (MRI) is the most suitable technique, and micron-sized iron oxide particles (MPIOs) used for labeling are favorable due to their low detection limit. However, constitutional data concerning labeling efficiency, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 47 publications
(126 reference statements)
1
41
0
Order By: Relevance
“…Due to this increased number of applications in biological systems, assessment of the sensitivity, toxicity, and adverse effects of NPs on cell biology has become a topic of interest. An extensive number of studies have evaluated the effect of NP labeling on cell homeostasis; some of which have pointed to negative effects of particle incorporation on cell viability, 38 actin cytoskeleton structure, 39 differentiation potential, 40,41 receptor expression, 42,43 migratory capabilities, 44,45 and reactive oxygen species (ROS) generation, 46 suggesting the need for in vitro evaluation before their in vivo application. The number of studies focusing on cell-related rather than NPrelated parameters is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this increased number of applications in biological systems, assessment of the sensitivity, toxicity, and adverse effects of NPs on cell biology has become a topic of interest. An extensive number of studies have evaluated the effect of NP labeling on cell homeostasis; some of which have pointed to negative effects of particle incorporation on cell viability, 38 actin cytoskeleton structure, 39 differentiation potential, 40,41 receptor expression, 42,43 migratory capabilities, 44,45 and reactive oxygen species (ROS) generation, 46 suggesting the need for in vitro evaluation before their in vivo application. The number of studies focusing on cell-related rather than NPrelated parameters is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The clinically approved dextran-coated SPIO are biodegradable [13], whereas polymer-embedded MPIO are supposedly bio-inert [14]. Several studies have shown that neither type of particle affects the cellular viability or metabolic activity of labeled cells [12,[15][16][17][18], but some recent studies have found adverse effects after administration of SPIO-labeled cells [19][20][21][22]. For MPIO, which have not been investigated to that extent, concerns remain with respect to their large iron core.…”
Section: Introductionmentioning
confidence: 95%
“…Due to this differentiation potential combined with their nonimmunogenic characteristics, MSCs are promising therapeutic tools in regenerative medicine 2 ISRN Stem Cells and tissue engineering [6][7][8][9] and thus also for therapeutic strategies in osteoporotic patients.…”
Section: Introductionmentioning
confidence: 99%